PENGARUH KUALITAS PELAYANAN GANTI METER PASCABAYAR DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA ULP PULANG PISAU KALIMANTAN TENGAH - Sadikin; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Jurnal Riset Multidisiplin Edukasi, 2026)
Service is a crucial element in efforts to increase customer satisfaction. Essentially, this service position is a supporting factor for PT. PLN (Persero)'s marketing activities. In order to improve the electricity supply services provided by PT. PLN (Persero) to the public in general and customers in particular. The purpose of this study is to test and analyze: 1. The influence of postpaid meter replacement service quality on customer satisfaction at ULP Pulang Pisau, Central Kalimantan. 2. The influence of company image on customer satisfaction at ULP Pulang Pisau, Central Kalimantan. 3. The influence of postpaid meter replacement service quality and company image on customer satisfaction at ULP Pulang Pisau, Central Kalimantan. This study employed a quantitative descriptive method. The population consisted of 280 customers who replaced postpaid meters at the Pulang Pisau ULP in Central Kalimantan. The sample size was determined using the Slovin formula, resulting in 74 customers. The sampling technique used was accidental sampling. Simple linear regression was used for data analysis. Based on the research results, the results of this study indicate that: 1. The quality of postpaid meter replacement services partially has a significant effect on customer satisfaction at the Pulang Pisau Central Kalimantan ULP. 2. Company image partially has a significant effect on customer satisfaction at the Pulang Pisau Central Kalimantan ULP. 3. The quality of postpaid meter replacement services and company image simultaneously have a significant effect on customer satisfaction at the Pulang Pisau Central Kalimantan ULP.